The Influence of Leadership, Work Culture, and Performance Assessment in Improving the Quality of Education: A Literature Review of SLR - Danisma, Danisma; Sales, Rocky Nathaniel R (Educational Leadership and Management Journal, 2025)
Leadership is an important element in supporting improving the quality of education. This research aims to identify the Influence of Leadership, Work Culture, and Performance Assessment in Improving the Quality of Education. The method used in this study is Systematic Literature Review (SLR) which is taken from articles published in 2020 to 2024 by collecting and analyzing journals related to keywords. The results of this study show that leadership, work culture, and performance assessment have a significant role in improving the quality of education. In education Effective leadership can motivate teachers and staff, a positive work culture encourages a sense of community, which both ensures understanding and involvement of all parties, while performance appraisals help identify strengths and areas for improvement and of course this can affect the quality of education. The leadership of the principal is essentially a principal who understands and masters managerial and effective leadership abilities as acronymized as the principal as a leader (educator, manager, administrator, supervisor, leader, innovator, and motivator). However, it is still a general problem that educational institutions experience several obstacles in improving the quality of education. The purpose of this study is to describe the literature in general, analyze the themes studied in several articles, and classify the limitations of the research and look for future research opportunities The combination of effective leadership, positive work culture, strategic communication, and continuous performance appraisal is the main foundation in improving the quality of education. This research makes a significant contribution to Digital Literature on leadership, work culture, and assessment of educational quality performance. Keywords: Leadership, Work Culture, Performance Assessment, Improving the Quality of Education